The relationship between depressive symptoms and sleep quality in medical staff after their infection with COVID-19 - Memarian, Amirhossein; Shahrbabaki, Parvin Mangolian; Zakeri, Mohammad Ali; Ahmadinejad, Mehdi (Frontiers in Psychiatry, 2023)
Background Healthcare workers (HCWs) play a crucial role in managing infectious diseases like COVID-19. However, the demanding working conditions during the pandemic have led to an increased risk of depression and sleep disorders among these dedicated professionals. Therefore, this study aimed to examine the relationship between depressive symptoms and sleep quality in medical staff who had contracted COVID-19. Methods This descriptive study involved a sample of 203 HCWs who had contracted COVID-19. These HCWs were employed at a hospital affiliated with Kerman University of Medical Sciences in 2020. The data for this study were collected using a demographic information form, the Pittsburgh Sleep Quality Index (PSQI), and the Beck Depression Inventory (BDI). Statistical analysis was conducted using SPSS22, with a significance level set at less than 0.05. Results The study found that the mean score for depressive symptoms among the participants was 11.67 ± 2.68, while the mean score for sleep quality was 5.47 ± 3.02. It was observed that 18.2% of the participants experienced moderate depression, 10.3% had severe depression, and 59.6% had poor sleep quality. Furthermore, a significant and positive correlation was identified between sleep quality and depression (r = 0.54; p = 0.001). Multiple regression models indicated that the harmful pattern and sleep quality together could predict 34% of the variance in depression. Additionally, the use of sedatives and depression were found to predict 33% of the variance in sleep quality. Conclusion The findings of our study indicated a high prevalence of depressive symptoms and insomnia among medical staff who had contracted COVID-19. These results provide valuable insights for health managers, highlighting the need for implementing interventions in epidemic environments to reduce the vulnerability of HCWs.